2008
DOI: 10.1007/s10803-008-0663-6
|View full text |Cite
|
Sign up to set email alerts
|

Restricted and Repetitive Behaviours, Sensory Processing and Cognitive Style in Children with Autism Spectrum Disorders

Abstract: Many individuals with autism tend to focus on details. It has been suggested that this cognitive style may underlie the presence of stereotyped routines, repetitive interests and behaviours, and both relate in some way to sensory abnormalities. Twenty-nine children with diagnosis of high functioning autism or Asperger syndrome completed the Embedded Figures Test (EFT), and their parents the Short Sensory Profile and Childhood Routines Inventory. Significant correlations were found between degree of sensory abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 33 publications
13
96
0
7
Order By: Relevance
“…However, as detailed below, studies that have investigated the association between a detailed-processing style and the symptoms of ASD have produced mixed results. Chen et al (2009) found a link between a detail-focused processing style in the visual domain and degree of repetitive behaviour in children with ASD. However, there was no relation between detail-focused processing and sensory processing abnormalities.…”
Section: And Asd Symptomsmentioning
confidence: 85%
“…However, as detailed below, studies that have investigated the association between a detailed-processing style and the symptoms of ASD have produced mixed results. Chen et al (2009) found a link between a detail-focused processing style in the visual domain and degree of repetitive behaviour in children with ASD. However, there was no relation between detail-focused processing and sensory processing abnormalities.…”
Section: And Asd Symptomsmentioning
confidence: 85%
“…Situational familiarity is particularly important when collecting data with people on the autism spectrum (Chen et al, 2009). Only the participant and the researcher were present.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that children with ASD who experience sensory processing abnormalities may also experience more repetitive behaviours (e.g. Chen, Rodgers, & McConachie, 2009;Baker et al, 2008). Repetitive behaviours may be functional in regulating arousal levels for children with ASD who experience sensory processing abnormalities (e.g.…”
Section: Exploring the Relationship Between Sensory Processing And Rementioning
confidence: 99%